Unraveling the pivotal role of amylopectin in enhancing hydrothermal stability and filtration control of native corn starch-based drilling fluids for decarbonization - Fuchang You; Lei Pu; Yu Wu; Yancheng Zheng (Fuel Processing Technology, 2025)
Enhanced utilization of native starch offers a promising approach to improving energy efficiency and advancing decarbonization, thereby fostering sustainable and eco-friendly practices in petroleum extraction. However, previous studies suggest limited high-temperature potential of native starch in water-based drilling fluids (WBDFs), mainly due to insufficient research on amylose-to-amylopectin ratios. This study investigates the hydrothermal stability and filtration control performance of corn starches with different amylose-to-amylopectin ratios in WBDFs to address this issue. The results demonstrate that amylopectin content significantly influences the hydrothermal stability and filtration control performance of WBDFs. Waxy corn starch, with 100 % amylopectin content, exhibits excellent performance, achieving a filtration loss of only 7.2 mL even at 160 °C. In contrast, as the amylopectin content decreases, the temperature resistance of normal corn starch declines below 140 °C, while high-amylose corn starch shows poor filtration control even at 120 °C. The key factor contributing to these differences is the amylopectin content. The “clustered or chrysanthemum-like” structure and multi-branched chains of amylopectin enhance bentonite interactions, improving colloidal stability and particle distribution. Slower degradation of amylopectin also boosts hydrothermal stability and dense mud cake formation. The findings of this study provide a theoretical framework for utilizing native starch in WBDFs.